Perencanaan Bahan Baku Produksi Menggunakan Metode Material Requirement Planning (MRP) Studi Kasus Teh Botol Sosro - Simanjuntak, Sarah Stefhanie; Zaharuddin, Zaharuddin; Puspita, Riana (Fakultas Teknik Universitas Tulang Bawang, 2024)
Raw material inventory is a serious problem for manufacturing companies. Shortages of raw materials can stop production, while inventories that are too large cause high storage costs and result in idle capital. Therefore, research entitled